Nest-building and breeding behaviour of house-farmed white-nest swiftlets aerodramus (Aves:apodidae) in Miri, Sarawak, Malaysian Borneo - Mohamad Fizl Sidq, Ramji. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Nesting and roosting behaviours are integral parts of breeding ecology of any bird speCIes. Although information on Sornean cave swiftlets is readily available in abundance since more than half a century ago, the same cannot be said for the house-farmed colony. Studies on nesting and breeding behaviour of this population are so far lacking. Despite all, numerous establishment of swiftlet houses across Malaysia have been propagated by the lucrative 'birds' nest' industry. My original contribution to the knowledge on ecology of the house-farmed white-nest swiftlet includes four key findings: (i) pattern of emergence and return, (ii) behaviours at nest or roost site, (iii) nestbuilding behaviours and (iv) parental behaviours and investments. This study was conducted in two separate house-farmed colonies in Miri Division, Sarawak from June 2010 to March 2011 (Site-I) and February 2012 to October 2012 (Site-II). Two types of infra-red (lR) cameras were used, namely (i) fixed focal-lens IR to monitor large colony and (ii) Pan-Tilt-Zoom (PTZ) camera for close-up observation. The first key finding reports a new discovery that describes three basic activity sessions beginning with the first-emergence period (0600-0700 hr), post-emergence period (0700-1000 hr) and returning period (1800-1900 hr). During the post-emergence period, approximately half of the sampled colony was observed re-entering the swiftlet house to resume nest construction. Secondly, the general behaviours were established by classifying three primary behavioural types which are roosting behaviours, nesting behaviours and parental behaviours. Twelve ethogram categories were developed to describe these behaviours: (i) proximity fluttering, (ii) random roosting flight, (iii) pair switching, (iv) parallel shifting, (v) mounting, (vi) preening, (vii) defecating, (viii) resting, (ix) territorial display, (x) nest-building (xi) incubation and (xii) feeding of young. The third outcome was derived from detail observation on a marked pair (PairAS) which revealed that there is a disparity in sexual contribution in nest-building activity.